The acquisition of intensifiers : emphatic reflexives in English and German child language - Gülzow, Insa, 1967- (Studies on language acquisition ;, 2006)
How do young children negotiate and comment on their participation in a given event? The study presented gives an insight into German and English children's use of intensifiers and related expressions at early stages of language development. The longitudinal production data of six German-speaking and six English-speaking children is examined with regard to when and in which contexts the intensifiers German selbst/selber and English x-self (myself, yourself, himself, etc.) appear. It is demonstrated that by integrating intensifiers into their utterances, children develop an important linguistic.